Freshwater vertebrate and invertebrate diversity patterns in an Andean-Amazon basin: implications for conservation efforts - Lessmann, Janeth (2016)
The Napo Basin in Ecuador is an important drainage of the Amazon Basin, the most biodiverse ecosystem for freshwater species. At the same time, this basin has conspicuous information gaps on its biodiversity patterns and human threats. Here, we estimated the diversity distribution patterns of freshwater vertebrates and invertebrates in the Napo Basin, as a tool for present and future management and conservation efforts. Also, we assessed the spatial congruence of the diversity patterns observed between aquatic vertebrates and invertebrates. For this, we compiled occurrence records for 481 freshwater vertebrate species (amphibians, birds, mammals, reptiles, and fish), and 54 invertebrate families obtained across an altitudinal gradient of the basin (200–4500 m). Using these occurrence records and environmental variables, we modeled the distribution of each vertebrate species and invertebrate family. Then, we stacked these distributions to build species richness maps for vertebrates, and a family richness map for invertebrates. We found that the most diverse areas for vertebrate species are the lowlands (<600 m), whereas richness of invertebrate families peaks at higher elevations (lower montane forests). Congruence among species richness patterns of the five vertebrate groups was high (r = 0.66), with fish being the best predictor for vertebrates (r = 0.78). However, congruence decreased at higher elevations (r = 0.14), suggesting that specific species or habitat-based approaches should be used in the highlands. Also, we found a high correlation between species and family richness of freshwater invertebrates (r = 0.66), suggesting that family richness of invertebrates could be used as a surrogate of species richness in this basin. We highlight this correlation because, at the watershed scale, it allows working with family groups where species-level taxonomy is challenging. Our results provide the first comprehensive representation of freshwater biodiversity patterns at high resolution in an Andean-Amazon basin, and calls attention to the need for incorporating different taxonomic groups when assessing diversity patterns. Given these different diversity patterns, conservation programs for this basin should incorporate both vertebrate and invertebrate groups as biodiversity indicators. Finally, our study provides a practical methodological guidance in the estimation of freshwater diversity in regions of scarce information with high conservation priority, such as the Andean-Amazon basins.